2001
DOI: 10.3109/15419060109080729
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cytoskeletal Elements in the Recruitment of Cx43-GFP and Cx26-YFP into Gap Junctions

Abstract: Cytoskeletal elements may be important in connexin transport to the cell surface, cell surface gap junction plaque formation and/or gap junction internalization. In this study, fluorescence recovery after photobleaching was used to examine the role of microfilaments and microtubules in the recruitment and coalescence of green fluorescent protein-tagged Cx43 (Cx43-GFP) or yellow fluorescent tagged-Cx26 (Cx26-YFP) into gap junctions in NRK cells. In untreated cells, both Cx26-YFP and Cx43-GFP were recruited into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 13 publications
(5 reference statements)
0
35
1
Order By: Relevance
“…In these studies, these pathways were distinguished by their differential pharmacologic sensitivity to brefeldin A which disassembles the Golgi (but did not block Cx26 transport) and nocodazole, a microtubule disrupting reagent (which blocked Cx26) Martin et al, 2001). However, these conclusions are controversial and not consistent with other published data (Thomas et al, 2001;Johnson et al, 2002). We tested these agents in our coexpressing cells.…”
Section: Oligomerization Of Cx26 and Cx43 In Co-expressing Cellscontrasting
confidence: 47%
“…In these studies, these pathways were distinguished by their differential pharmacologic sensitivity to brefeldin A which disassembles the Golgi (but did not block Cx26 transport) and nocodazole, a microtubule disrupting reagent (which blocked Cx26) Martin et al, 2001). However, these conclusions are controversial and not consistent with other published data (Thomas et al, 2001;Johnson et al, 2002). We tested these agents in our coexpressing cells.…”
Section: Oligomerization Of Cx26 and Cx43 In Co-expressing Cellscontrasting
confidence: 47%
“…After disrupting microtubules with nocodazole, Cx43 assembly was hardly affected in transfected HeLa cells, whereas Cx26 assembly was inhibited [Martin et al, 2001]. Nocodazole treatment also affected Cx43 recruitment in GJs, whereas Cx26 transport and clustering remained nearly unchanged [Thomas et al, 2001]. Inhibition of Cx transport in the Golgi by brefeldin A and inhibition of microtubules by nocodazole in Cx43-transfected HeLa cells blocked GJ assembly after the pool of non-junctional hemichannels in the plasma membrane was depleted.…”
Section: Shuttling To the Plasma Membrane And Intramembrane Movementmentioning
confidence: 99%
“…We previously showed that this treatment condition completely depolymerized microtubules in NRK cells (Thomas et al, 2001). We quantified the movement of vesicles containing fluorescent-protein-tagged Cx43 or Cx26 and found that in both cases there was an ~80% decrease in vesicle movement when microtubules were disrupted (Table 1 and supplementary material Movie 7).…”
Section: Differential Mobility Of Cx43 and Cx26 Within Gap Junction Pmentioning
confidence: 99%
“…To analyze the role of microtubules in vesicular connexin transport, NRK cells expressing fluorescentprotein-tagged Cx43 or Cx26 were first time-lapse imaged (32 second image acquisition intervals) for up to 18 minutes. After treating the cells for 45 minutes with nocodazole (10 M) to disrupt the microtubules (Thomas et al, 2001), the same field of cells was again time-lapse imaged over an additional period of up to 18 minutes. LSM 510 software was used to calculate the individual vesicle displacement over 1 minute from time-lapse images of cells before and after microtubule disruption as modified from the procedure described previously (Johnson et al, 2002).…”
Section: Drug Treatments: Bfa and Nocodazolementioning
confidence: 99%